Handbook of sputter deposition technology fundamentals and applications for functional thin films, nano-materials and MEMS - Adachi, Hideaki; Wasa, Kiyotaka; Kanno, Isaku; Kotera, Hidetoshi (William Andrew, 2012)
This thoroughly updated new edition includes an entirely new team of contributing authors with backgrounds specializing in the various new applications of sputtering technology. It forms a bridge between fundamental theory and practical application, giving an insight into innovative new materials, devices and systems. Organized into three parts for ease of use, this Handbook introduces the fundamentals of thin films and sputtering deposition, explores the theory and practices of this field, and also covers new technology such as nano-functional materials and MEMS.